2020
DOI: 10.1021/acs.langmuir.9b03988
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Color Coating of E-Textiles by Atomic Layer Deposition of Multilayer TiO2/Al2O3 Films

Abstract: We successfully fabricated a conductive E-textile and color-coated E-textile by depositing multilayer Al 2 O 3 /TiO 2 on a conductive E-textile through atomic layer deposition (ALD). Pt was deposited on an E-textile as a conductive layer via lowtemperature ALD. The color of the coated conductive E-textile could be tuned to violet, green, or pink by simply varying the thickness of the Al 2 O 3 and TiO 2 layers. Both experimental and simulation results revealed that seven different colors can be obtained with si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Our first challenge is related to the fact that each type of TiO 2 /Al 2 O 3 stacking and all types of Al doping form unique films with specific properties, structures and growth forms. Another difficulty faced is due to the large number of articles that study the application of these materials (more than 100 works were found), ranging from microelectronics [ 54 , 61 , 62 , 84 ] to application in tunable color coating [ 38 ], which makes it difficult to compare with the present work. Finally, we found about 11 works that can be compared.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our first challenge is related to the fact that each type of TiO 2 /Al 2 O 3 stacking and all types of Al doping form unique films with specific properties, structures and growth forms. Another difficulty faced is due to the large number of articles that study the application of these materials (more than 100 works were found), ranging from microelectronics [ 54 , 61 , 62 , 84 ] to application in tunable color coating [ 38 ], which makes it difficult to compare with the present work. Finally, we found about 11 works that can be compared.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, ALD stands out for its unique capabilities, which include the complex shapes coverage embedded in high conformal 3D areas [ 23 ], the growth of stacked monolayers of different nanomaterials [ 24 ], and the growth of thin films precisely defined by self-limited surface reactions [ 25 , 26 , 27 , 28 , 29 ]. The ALD’s versatility allows its application in a broad range of fields, such as micro and nanoelectronics [ 30 , 31 ], biomedical engineering [ 32 ], on food packaging against corrosion [ 33 , 34 ], fuel cells [ 35 ], solar cells [ 36 ], anti-tarnish coatings on jewels surfaces [ 37 ], smart textiles [ 38 ], membranes, and optoelectronics [ 39 , 40 , 41 ]. Despite the wide range of applications of the ALD technique, fundamental studies are needed to understand essential aspects of the chemical, morphological, mechanical, and optical properties of the thin films that influence devices’ properties and their applications.…”
Section: Introductionmentioning
confidence: 99%
“…Functionalities explored over the past couple of decades include bacterial resistance [20] , ease of dyeing [21] , hydrophobicity [22] , flame retardancy [3] , UV protection [23] , colorfastness [24] and ability for self-cleaning [25] . As described below, an area of intense current activity is to develop fabrics, and hence garments, that can harness, store and deliver energy to the wearer to power daily activities.…”
Section: Current Research Trends For Smart Textilementioning
confidence: 99%
“…Examples that have been used include polyacetylene, polypyrrole, polyaniline [5] , Au [6] , Ag [7] , Pd [8] , Cu [9] , Si [10] , CuO [11] , ZnO [12] , carbon nanotube (CNT) [13] , [14] , TiO 2 [15] , [16] , chitosan [17] , MXenes [18] and graphene oxide (GO) [19] nanoparticles. Textiles modified with these nanomaterials have potential applications in wound healing [23] , [24] , air purification [25] , drug delivery [24] , cosmetics, renewable energy generation and electronic applications such as fabrication of on-body diodes, transistors and circuitry [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Different fabrication methods based on coating [155]- [156], spinning [157]- [158], plating [159], printing [160]- [161] and injecting [162], have been used to produce electrical textiles. The most common are the melt-spinning and the electrospinning processes.…”
Section: ) Piezoelectricitymentioning
confidence: 99%